Seven Dimensions Of Accountability In Iran's Teaching Hospitals: A National Study - Mohammad Mahboubi; Amirashkan Nasiripour; Seyed Jamalodin Tabibi; Mahmudreza Gohari (Tehran University of Medical Sciences, 2012)
Background and Aim: Accountability is a process by which all service organizations including hospitals are required to legitimize their activities. This research aims to study the seven aspects of accountability in Iran's teaching hospitals. Materials and Methods: This is a cross-sectional analytic study performed in the second half of 1390 in five major medical-educational hospitals in 5 points of the country. A research-made questionnaire with seven dimensions (ethical, cultural, financial, operational, legal, informational, and structural) was used. The collected data were analyzed using descriptive and inferential statistics. Results: The total number of subjects was 454, of whom 45.6% were males and the rest were females (n = 247). They were mostly (40.1%) in the age group of 21- to 29-year-olds, and the least figure (6.8%) pertained to those older than 50 years of age. The average mean of structure turned out to be the highest (3.54 ± 0.97) and the informational dimension had the lowest (3.45 ± 0.97). The average accountability score was the highest in Rasht hospital (99.3 ± 0.61) and the lowest in Tehran hospital (3.02 ± 0.67). The correlations between all dimensions were confirmed. Moreover, accountability as evaluated in the studied educational hospitals was above average. Conclusion: Patients' attitude towards accountability in Iran's teaching hospitals was assessed to be above average. The findings show that an office or a unit for accountability, validation, and continuous audit of its dimensions is essential to advance the high goals of the hospitals.